Comparison of the Effects of Injectable and Implant Progestin Contraceptive Agents on Weight Increase Based on Body Mass Index (BMI) in Family Planning Acceptors in District - Sukarni Setya Yuningsih; Atika Juliarni; Desti Indayani; Mega Yanti Erdha; Milda Anggraini; Nur Afni (Postgraduate, University of Mataram, 2024)
Weight gain is one of the side effects that birth control acceptors often worry about, especially users of hormonal methods such as progestin injections and implants. This concern is reasonable because several studies show that the use of hormonal contraception can increase the risk of weight gain. This study aims to compare the use of progestin injections and implants on weight gain based on Body Mass Index (BMI) in family planning acceptors in Muara Enim Regency in 2024. The research sample consists of 266 respondents who are acceptors of birth control injections and implants, with an observational analytical research design using a case control design. The sample size was determined using the G-Power Software application Version 3.1.6 with correlation and regression tests. The results of the analysis show that family planning acceptors with progestin injectable contraceptives have a 1.68 times greater chance of experiencing abnormal weight gain (obesity) compared to family planning acceptors who use implants (95% CI 1.021-2.752). It is hoped that the results of this research can be used as a reference for midwives to provide education regarding the negative impact of weight gain on family planning acceptors, so that they can inform more appropriate hormonal contraceptive choices.